Cardiorespiratory and endocrine effects of endogenous opioid antagonism by naloxone in ponies anaesthetised with halothane - Luna, SPL; Taylor, P. M. (W B Saunders Co Ltd, 2001)
Halothane depresses cardiorespiratory function and activates the pituitary-adrenal axis, increasing beta endorphin. In horses, beta endorphin may enhance the anaesthetic-associated cardiorespiratory depression and mortality risk. The authors studied endogenous opioid effects on cardiorespiratory function and pituitary-adrenal activity in halothane-anaesthetised ponies by investigating opioid antagonism by naloxone. Six ponies were anaesthetised three times (crossover design). Anaesthesia was induced with thiopentone and maintained with 1.2 per cent halothane for 2 hours. Immediately after induction, naloxone was administered either intra venously (0.5 mg kg(-1) bolus then 0.25 mg kg(-1) hour(-1) for 2 hours) or intrathecally (0.5 mg) or was replaced by saline as control. Pulse and respiratory rates, arterial blood gases, cardiac output and plasma cortisol and adrenocorticotrophic hormone (ACTH) concentrations were measured. All groups developed cardiorespiratory depression (40 per cent decrease in cardiac output) and plasma cortisol increased. Plasma ACTH concentration was higher in ponies treated with intrathecal naloxone. Endogenous opioids may inhibit ACTH Secretion, attenuating the stress response to halothane anaesthesia in equidae. (C) 2001 Harcourt Publishers Ltd.